К проблеме воздействия Востока на Скандинавию и Русь в раннем средневековье - Пушкина, Т.А. (Хазарский альманах, 2020)
Swedish archaeologist T. Arne was fi rst who examined the contacts of North Europe and East in 1914. He considered appearance of the belts, decorated with the metallic platelets of the Khazarian origin in Scandinavia as result of these contacts. The collection of the objects of the “Eastern origin” is diverse and waist of the belts set is a small fraction of the archaeological material. Unique for ancient Russia as well as for the Viking age Scandinavia objects could appear there as the trophies of the military marches of the Russians and Scandinavians, who were part of Old-Russian retinue.